An annotated checklist of flora of Overa-Aru wildlife sanctuary, Kashmir Himalaya - Islam, Tajamul; Khuroo, Anzar Ahmad; Nawchoo, Irshad A. (Phytotaxa, 2023)
The Overa-Aru wildlife sanctuary is one of the largest protected areas in terms of area (425 km2) in Kashmir Himalaya. Here, we present an annotated checklist of flora of the sanctuary, which includes 397 taxa (392 species, 1 subspecies, 3 varieties and 1 forma) belonging to 254 genera in 76 families. Asteraceae was the dominant family with 57 species, followed by Rosaceae and Lamiaceae with 28 and 27 species respectively. Likewise, Salix and Veronica were the dominant genera with 7 species each, followed by Artemisia with 6 species. The herbs were dominant (307 species, 77.33%) followed by trees (41, 10.33%). Lifespan wise, perennials were dominant (318 species, 80.1%), followed by annuals (66, 16.62%). The hemicryptophytes were the dominant life forms (224 species, 56.42%), followed by phanerophytes (80, 20.15%). Further, nine species occurring in sanctuary are currently recognized under different IUCN threat categories. The checklist provides the first-ever comprehensive documentation of the flora from this Kashmir Himalayan protected area, supplemented with details on natural life-history traits and up-to-date conservation status. Hopefully, the study will be immensely useful in guiding suitable conservation strategies and management planning of protected areas in the region.